Safety of Bivalirudin Use in Critically Ill Children: A Single-Center Experience - Dalia A. Bashir; Javier Leija; Rayhan N. Jhanji; Jacquelyn M. Powers; Katherine I. Lemming; Sarah E. Sartain; Duy M. Dinh; Clay T. Cohen (Pediatric Critical Care Medicine, 2026)
Objectives: Bivalirudin, an IV direct thrombin inhibitor, is increasingly used as an alternative anticoagulant in pediatric patients on mechanical circulatory support, with heparin failure, or for heparin-induced thrombocytopenia. Data on its use for treatment or prevention of venous or arterial thromboses in children are limited. To describe the safety of bivalirudin in critically ill children for the treatment or prevention of venous and/or arterial thromboses. Design: Retrospective review of patients under 18 years treated with bivalirudin between January 2019 and August 2024. Setting: Quaternary care Children’s Hospital. Patients: Descriptive analyses were conducted for all patients receiving bivalirudin. Primary outcomes include bleeding and thrombotic events. Secondary outcomes included time to therapeutic levels, dosing, and the association of therapeutic laboratory goals (via Partial Thromboplastin Time Hepzyme [PTTHz] and dilute thrombin time-derived bivalirudin levels) with adverse events. Intervention: None. Measurements and Main Results: A total of 261 bivalirudin encounters in 229 patients were included in the analysis (median age, 0.51 yr; interquartile range, 0.13–3.92 yr). The most common indication was treatment of venous thrombosis ( n = 133, 51%). Eighty-six bleeding events occurred in 261 encounters (33%) involving 61 of 229 patients (27%); 20 of 86 bleeding events were considered major (23.2%). Thrombotic progression or development of new thrombi occurred in 46 of 261 (17.6%) encounters (37/229; 16% patients) with 18 of 261 experiencing both bleeding and thrombotic events. Therapeutic PTTHz/bivalirudin levels were observed in 56.5% (26/46) of new thromboses/thrombotic progression and 57% (49/86) of bleeding events. Median starting dose and dose at first therapeutic level were 0.15 and 0.2 mg/kg/hr, respectively. Median time to achieve therapeutic anticoagulation was 0.56 days. Conclusions: Bivalirudin, used in the setting of venous and/or arterial thromboses, rapidly achieves therapeutic levels. While use of bivalirudin is safe, clinically relevant bleeding and thrombotic rates on bivalirudin were frequent despite therapeutic ranges. These data highlight that bivalirudin use warrants close monitoring in critically ill children.